Pasar Uang Berdasarkan Prinsip Syariah (Fatwa Dewan Syariah Nasional No.37/DSN-MUI/IX/2002) - Utami, Dian; Apryliani , Apryliani Usman; Wirna; Octavia, Ismi; Nurhaliza; Runtuwene, Dwi Windi (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2022)
The money market serves as a nexus for financial transactions between two parties: one with surplus funds and the other lacking adequate funds. From an Islamic perspective, the employment of an interest rate system is prohibited. Instead, Islamic finance principles advocate the use of contracts such as Musyarakah, Mudharabah, Al-sharaf, wadiah, Al-qard, gharar, and maysir to replace interest-bearing elements. The Islamic money market is a tangible manifestation of these principles, having garnered approval through the issuance of DSN Fatwa No. 37/DSN-MUI/IX/2002, which endorses the operation of the interbank financial market in accordance with Sharia principles.